Allele and haplotype diversity of 17 Y-STRs loci in the northern region Pashtun (Pathans) population of Pakistan. Issue 3 (3rd May 2016) - Saman, Asima; Wajid, Abdul; Wasim, Muhammad; Sara, Aysha; Salman, Muhammad; Uddin, Zia
Abstract : A total of 17 Y-linked short tandems repeat (Y-STRs) loci (DYS19, DYS385a, DYS385b, DYS389I, DYS389II, DYS390, DYS391, DYS392, DYS393, DYS437, DYS438, DYS439, DYS448, DYS456, DYS458, DYS635, and GATA H4) were genotyped in the Pashtun (Pathans) male population residing in the northern region of Pakistan. The Pashtun population, in spite of its decisive geographic location for repopulation movements between Pakistan, Afghanistan and India over time, has been insufficiently characterised at the genetic level, especially for Y chromosomal DNA variation. To understand the genetic structure characterisation of the Pashtun resident population of the northern region, we have utilised the Y chromosome STRs diversity, haplotype diversity and discrimination capacity. In this work, a total of 67 distinct haplotypes were observed in the resident population of Pashtun living in the northern region of the country, and they showed a high haplotype diversity (0.9756) and discrimination capacity (89.3%); five individuals shared a single haplotype. Genetic distances between the studied population and 11 other populations were calculated based on haplogroup frequencies with Analysis of Molecular Variance (AMOVA).